Problematics and Structuring of the DPRD in Local Government Administration - Anwar, Wildan Rofikil; Anggono, Bayu Dwi; Efendi, Aan (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
DPRD is said to be a regional legislative body because it has the authority to make local regulations, several local government laws that have been in force mention that DPRD has a legislative function, similar to the DPR. The filling of positions for DPRD members is also done together with the filling of positions for DPR members in legislative elections. This has created the impression that DPRDs and DPRs are both legislative institutions, even though they are different. To make the difference more significant, there must be a revision/reorganization of the Local Government Law. The purpose of this research is to understand and find out about the problems and structuring of DPRD in the implementation of local government. The type of research used is normative juridical, while the approaches used in this research are three, namely legislative approach, conceptual approach, and historical approach. The results of the research in this journal are that the DPRD as an organizing institution of local government should be regulated in the Local Government Law together with the regional head and not regulated in other laws such as the MD3 Law. The Local Government Law also needs to organize the functions of the DPRD where the first order of functions should be the functions of supervision, budgeting, and the formation of local regulations. This is because DPRDs more often or routinely carry out supervisory functions, rather than budgetary and local regulation formation functions. The filling of the positions of DPRD members is carried out simultaneously with the positions of regional heads, not through elections together with members of the DPR. The nomenclature of DPRDs should also be changed, i.e. Provincial DPRDs should be changed to Provincial Councils, while DPRDs at the Regency/City level should be changed to Regency/City Councils. Suggestions in this research are aimed at making a new law on legislative institutions that does not include provisions on DPRDs, considering that DPRDs are not legislative institutions, but regional government organizing institutions.